The Academi Library´contribution to the plans and projects of the institution - Alonso-Arévalo, Julio; Vázquez-Vázquez, Marta (Cuadernos de Documentación Multimedia, 2018)
Academic libraries exist within the context of their specific institutions and share with these broader political, social and policy environments. The effects of technological innovation have been rapid, significant and well-documented; consequently, libraries have responded positively to these changes in the way people read, communicate and research by providing digital content and renewing spaces to support their users’ new work and information needs. The article includes some contributions and studies that demonstrate the value of the cadademic library for its institutions and users, as well as the most relevant future trends in this context